Athletic identity and disordered eating in obligatory and non-obligatory runners - Gapin, J. I.; Petruzzello, S. J. (Journal of Sports Sciences, 2011)
Athletic identity is the extent to which an individual identifies with being an athlete. Strong "running" role identity may contribute to increased restrictive dieting behaviours, potentially placing such individuals at risk for eating disorders. In this study, we examined differences in eating and exercise behaviours/attitudes and athletic identity in obligatory versus non-obligatory runners. Male and female participants completed a battery of questionnaires including the Eating Disorder Inventory, Obligatory Exercise Questionnaire (OEQ), and Athletic Identity Measurement Scale (AIMS). OEQ scores =50 were indicative of obligatory exercise. The non-obligatory runners (n = 82) and obligatory runners (n = 91) were compared on the various measures. Obligatory runners scored significantly higher (P < 0.002) on all of the eating attitudes/disorder measures, and the AIMS (P = 0.006). Scores on the AIMS were correlated with all disordered eating measures (P < 0.05). Exercising to maintain identification with the running role may be associated with pathological eating and training practices.